HEPATITIS C SEROCONVERSION RATES IN PATIENTS ON HEMODIALYSIS IN TERTIARY CARE HOSPITALS: A MULTICENTER CROSS SECTIONAL STUDY - Asif, Muhammad; Zahid, Muhammad; Ahmad, Raheel; Mehmood, Zafar; Din, Zia -Ud-; Muhammad, Ali (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the rates of HCV seroconversion in patients undergoing hemodialysis (HD) in dialysis units of tertiary care hospitals.Study Design: Descriptive cross-sectional study.Place and Duration of Study: Dialysis units of three tertiary care hospitals, from Feb to Jul 2018.Methodology: Three hundred and sixty four (364) patients on hemodialysis for more than six months were included based on inclusion criteria. All these patients were HCV negative at the initiation of dialysis. All those patients who were HCV positive at the baseline or sero-converted within six months were excluded. Patients who became HCV positive later after six months were labeled sero-converted. Data about demographics, time sinceinitiation of HD and time to HCV seroconversion was collected through a structured questionnaire and retrieved retrospectively from patients medical record. Descriptive statistics were used to identify rate of HCV seroconversion and binary logistic regression used to estimate its determinants.Results: Of the total, 222 (61%) were males and 142 (39%) were females. The mean age (SD) of the participants was 43.76 years ± 15.86 (Range: 14-80 years). Mean (SD) duration since initiation of HD was 26.80 ± 27.99 months. Of the total, 145 (39.8%) seroconverted whereas 219 (60.2%) remained HCV negative. The mean (SD) time taken for seroconversion was 14.84 ± 11.58 (range: 6-60 months). Duration since initiation of HD was strongly associated with seroconversion (p